1974
DOI: 10.1021/jo00936a033
|View full text |Cite
|
Sign up to set email alerts
|

Quinazolines. XIII. Synthesis of polycyclic 2,4-diaminopyrimidines from aromatic amine hydrochlorides and sodium dicyanamide

Abstract: In an earlier communication, IV1,IV5-bis(2-naphthyl)biguanide hydrochlorides were reported to undergo a novel

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

1975
1975
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…An interesting reactivity involving dicyanamide was discovered in the early 1970s by Rosowsky et al [62]. Here, the authors observed an intramolecular aromatic electrophilic substitution under high-temperature conditions.…”
Section: Scheme 25mentioning
confidence: 90%
See 2 more Smart Citations
“…An interesting reactivity involving dicyanamide was discovered in the early 1970s by Rosowsky et al [62]. Here, the authors observed an intramolecular aromatic electrophilic substitution under high-temperature conditions.…”
Section: Scheme 25mentioning
confidence: 90%
“…Later, this S E Ar reactivity was used for the synthesis of pyrroloquinazoline from 5-aminoindole [63]. Contrary to the one-pot procedure published by Rosowsky et al [62], these authors performed the reaction in two steps, by isolating the 5-indolylcyanoguanidine intermediate, in higher overall yields (Scheme 28). Interestingly, the addition of 5-aminoindole hydrochloride to the dicyanamide proceeded smoothly at 40 °C in DMF with a 90% yield.…”
Section: Scheme 25mentioning
confidence: 99%
See 1 more Smart Citation